Reproductive and developmental toxicology - Gupta, Ramesh C. (Ramesh Chandra), 1949- (Amsterdam : Elsevier/Academic Press, 2011)
Reproductive toxicology is a complex subject dealing with three components-parent, placenta, and fetus-and the continuous changes that occur in each. Reproductive and Developmental Toxicology is a comprehensive and authoritative resource providing the latest literature enriched with relevant references describing every aspect of this area of science. It addresses a broad range of topics including nanoparticles and radiation, gases and solvents, smoking, alcohol and drugs of abuse, food additives, nutraceuticals and pharmaceuticals, and metals, among others. With a special focus on placental toxicity, this book is the only available reference to connect the three key risk stages, and is the only resource to include reproductive and developmental toxicity in domestic animals, fish, and wildlife.
Section-I: General -- Section-II: Safety Evaluation and Toxicity Testing Models -- Section-III: Nanoparticles and Radiation -- Section-IV: Gases and Solvents -- Section-V: Smoking, Alcohol, and Drugs of Abuse and Addiction -- Section-VI: Food Additives, Nutraceuticals, and Pharmaceuticals -- Section-VII: Metals -- Section-VIII: Pesticides and Other Environmental Contaminants -- Section-IX: Phytotoxicants -- Section-X: Biotoxins -- Section-XI: Special Topics -- Section-XII: Endocrine Disruption, Mutagenicity, Carcinogenicity, Infertility and Teratogenicity -- Section-XIII: Toxicologic Pathology -- Section-XIV: Placental Toxicity -- Section-XV: Domestic, Wildlife and Aquatic Species.
Keywords: Congenital Abnormalities -- embryology; Embryonic Development -- drug effects; Fetal Development -- drug effects; Toxicity tests